Novelties in central Amazonian microcaddisflies: Three new species of Ochrotrichia Mosely (Trichoptera: Hydroptilidae) - Moreno, Lucas; Desidério, Gleison Robson; Pes, Ana Maria; Hamada, Neusa (Zootaxa, 2021)
Ochrotrichia Mosely is the most species-rich group of microcaddisflies in the Neotropical Region. However, knowledge about this genus in Brazil is still limited; only 11 species are known, distributed in the Atlantic Forest (9), Caatinga (3), and Amazon (1) biomes. In this paper, three new species of Ochrotrichia are described and illustrated based on adult males collected in the Ducke Forest Reserve, a protected area administered by the Instituto Nacional de Pesquisas da Amazonia (INPA), located in central Amazonia, Brazil. Ochrotrichia belodes sp. nov., O. buenosoria sp. nov. and O. ducke sp. nov. can be recognized mainly by the morphology of tergum X and the inferior appendages. Based on their simple, elongate tergum X, all new species are assigned to the Ochrotrichia xena Group.